DIRECT SEEDED RICE: A CLIMATE-SMART AND ECONOMICALLY VIABLE SUBSTITUTE FOR PUDDLED TRANSPLANTED RICE IN GUNTUR DISTRIC - M , GANGA DEVI (The Journal of Research ANGRAU, 2026)
Direct seeding is becoming a key alternative transplanting in rice and has spread quickly inAndhra Pradesh, where unpredictable weather, fewer rainy days, lack of labor and higherproduction costs are common. This study looks at how changes in climate, such as variations inrainfall and temperature, recommend  the use of Direct-seeded rice (DSR) as a farming method.DSR involves planting rice seeds directly into the field instead of growing them in water and  thentransplanting them. The results show that using DSR options greatly improves rice productivityand resilience, while also saving labor, water, and energy. It also helps get the next crop started15 days earlier than the traditional puddled transplanted rice method. The study suggests thatadopting DSR can help maintain food security and crop resilience even in tough weather conditions.